Sigma Receptors Suppress Multiple Aspects of Microglial Activation - Hall Aaron, A. (2009)
During brain injury, microglia become activated and migrate to areas of degenerating neurons. These microglia release pro-inflammatory cytokines and reactive oxygen species causing additional neuronal death. Microglia express high levels of sigma receptors, however, the function of these receptors in microglia and how they may affect the activation of these cells remain poorly understood. Using primary rat microglial cultures, it was found that sigma receptor activation suppresses the ability of microglia to rearrange their actin cytoskeleton, migrate, and release cytokines in response to the activators adenosine triphosphate (ATP), monocyte chemoattractant protein 1 (MCP-1), and lipopolysaccharide (LPS). Next, the role of sigma receptors in the regulation of calcium signaling during microglial activation was explored. Calcium fluorometry experiments in vitro show that stimulation of sigma receptors suppressed both transient and sustained intracellular calcium elevations associated with the microglial response to these activators. Further experiments showed that sigma receptors suppress microglial activation by interfering with increases in intracellular calcium. In addition, sigma receptor activation also prevented membrane ruffling in a calcium-independent manner, indicating that sigma receptors regulate the function of microglia via multiple mechanisms.